Characterisation of ferritic to austenitic steel functional grading via powder hot isostatic pressing. (June 2022) - Stavroulakis, Emmanouil; Bowden, David; Irukuvarghula, Sandeep; Garner, Alistair; Pickering, Ed; Stewart, David; Preuss, Michael
Abstract: The application of functionally graded components produced via the powder hot isostatic pressing (HIP) process is considered for the next generation nuclear reactors as an alternative to dissimilar metal welding. This work is focused on functional grading of an SA508 Grade 3 ferritic low-alloy steel and 316L austenitic stainless steel, typically present in the pressure vessel and the piping or the pressure vessel cladding, respectively. Material was supplied in powder form, mixed and consolidated via the HIP process. Five different powder fractions were studied and, in some cases, significant change in the ferrite over austenite ratio is found to take place, due to dilution of austenite stabilizing elements. In contrast, the enrichment of alloying elements within the ferritic phase promotes the formation of laths, greatly affecting the material properties. The strengthening effect of the ferritic lath zone is assessed and the mechanism for its formation in the ferritic-austenitic system studied (throughout this work the term ferritic laths refers to a ferritic phase of unknown structure which is likely to consist of martensite, bainite or a mixture of both). Graphical Abstract: Example of a diffusion couple used to study diffusion bonding of SA508 grade 3 and 316L steels. The two steel blocks were extracted from respective HIP consolidated powder specimens. A hard zone was generated at the bonding interface. ga1